Freak to queer bodies: affirming the grotesque in contemporary art - Mello, Júlia (Frontiers in Sociology, 2025)
This article analyzes artworks that employ the grotesque to challenge hegemonic discourses. It draws a parallel between bodies depicted in 19th-century freak shows and queer bodies represented in artistic productions from the mid-1990s to the early 2000s. In both historical and modern contexts, bodily difference plays a pivotal role in defining normality. Various artistic endeavors have aimed to reconsider this premise, particularly by addressing gender issues, exemplified in the works of Brazilian artist Fernanda Magalhães and Chicana artist Laura Aguilar. This investigation employs image analysis, focusing on art history and visual culture, alongside a literature review. The findings suggest the potential for rethinking the social status of bodies labeled abnormal and highlight the political impact of contemporary art in promoting social inclusion.